Clinical communication skills in India: Current trends and future perspectives - Tooba Khursheed; L. V. Simhachalam Kutikuppala; Akatya Vidushi Sinha; Krishna Naineni (Wolters Kluwer -Medknow Publications, 2022)
Effective and sensitive communication by the clinicians with the patients and relatives are crucial in achieving a patient-centered consultation. Competent communication is an expertise, which all health-care professionals require, but it is the one that not all of them are obviously good at. Clinical communication skills are related to the speedy recovery of patients, provided with good adherence to the medications, and improved patient satisfaction, thereby affecting the psychological, biological, and social outcomes of the treatment. As time progressed, the situation of learning clinical communication skills has been transformed from "good to have" toward "need to have." Teaching soft skills of communication to the medical students in a controlled environment before exposing them to real-life conditions could be the key to developing rapport with the patients, leading to more appropriate diagnosis and treatment outcomes.